GC-MS Evaluation of Fatty Acid Profile and Lipid Bioactive of Partially Hydrogenated Cooking Oil Consumed in Pakistan: Evaluation of Cooking Oil (Biological Sciences - PJSIR, 2010)
Evaluation of fatty acid profile including trans fat and lipid bioactive (tocopherol and sterol contents) of most commonly used vanaspati ghee and cooking oil brands was made by gas chromatography coupled with mass spectrometer detector (GC-MSD). Among the saturated fatty acids (SFA), palmitic and stearic acid were dominant fatty acids; the mean value of SFA in ghee and oil was 44.98 and 30.83%, respectively. Mean values of monounsaturated, polyunsaturated and trans fatty acids in ghee were 47.51, 7.49 and 8.08%, and in oil 49.26, 19.90 and 0.91%, respectively. a-Tocopherol was the major tocopherol while campesterol, stigmasterol and sitosterol were main phytosterols in terms of their   quantity.